1982
DOI: 10.1107/s0567739482000515
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoatom expansions of the first-row diatomic hydride electron densities

Abstract: Representations of high-quality molecular electron densities are studied. An evaluation of restricted radial functions is made using a least-squares figure of merit, the molecular dipole and quadrupole moments, the electric fields at the nuclei, the electric-field gradients at the nuclei, an approximate energy and differencedensity maps. For the heavy atom, a satisfactory representation has a fixed core function with a variable population and requires optimized dipolar core polarization functions, and an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Tsirelson et al (2006) also made an accurate joint low-temperature X-ray diffraction and nonempirical quantum chemical study of bonding in (3), and obtained extensive bond and atomic quantum-topological descriptors. A comparison of the QTAIMC results obtained for (3) from accurate X-ray diffraction measurements, threedimensional periodic calculations (CRYSTAL98; Saunders et al, 1998) and single-molecule DFT B3LYP/6-311G(d,p) calculations confirmed earlier findings (Chandler & Spackman, 1982;Parini et al, 1985;Iversen et al, 1997;de Vries et al, 2000;Volkov et al, 2000;Volkov & Coppens, 2001;Flaig et al, 2002;Bytheway et al, 2002;Tsirelson et al, 2006) that the main differences between the experimentally and theoretically obtained properties are observed for the longitudinal ('along the bond path') ED curvature, 3 . This may be attributed to a deficiency of the ED description with current multipole models.…”
Section: Introductionsupporting
confidence: 76%
“…Tsirelson et al (2006) also made an accurate joint low-temperature X-ray diffraction and nonempirical quantum chemical study of bonding in (3), and obtained extensive bond and atomic quantum-topological descriptors. A comparison of the QTAIMC results obtained for (3) from accurate X-ray diffraction measurements, threedimensional periodic calculations (CRYSTAL98; Saunders et al, 1998) and single-molecule DFT B3LYP/6-311G(d,p) calculations confirmed earlier findings (Chandler & Spackman, 1982;Parini et al, 1985;Iversen et al, 1997;de Vries et al, 2000;Volkov et al, 2000;Volkov & Coppens, 2001;Flaig et al, 2002;Bytheway et al, 2002;Tsirelson et al, 2006) that the main differences between the experimentally and theoretically obtained properties are observed for the longitudinal ('along the bond path') ED curvature, 3 . This may be attributed to a deficiency of the ED description with current multipole models.…”
Section: Introductionsupporting
confidence: 76%
“…A significant discrepancy in the model and wavefunctionbased Laplacians of the electron density for shared interactions has already been noted in the literature (Bianchi et al, 1996;Spackman et al, 1999;Flaig et al, 2002;Zhurova et al, 2004;Henn et al, 2004;Hibbs et al, 2005). Insufficient flexibility of existing multipole models to span the charge distribution both close to the nuclei and at the middle-bond area (especially for polar covalent bonds) is considered to be the main reason for this discrepancy (Chandler & Spackman, 1982;Parini et al, 1985;Iversen et al, 1997;de Vries et al, 2000;Volkov et al, 2000;Volkov & Coppens, 2001), the maximum discrepancy being found for the ED curvature along the bond line, 3 ( Table 4 Atomic volumes (), charges (Q) and electronic energies (H) integrated within the atomic basins.…”
Section: Molecular and Crystal Structurementioning
confidence: 99%
“…In order to explore the best procedure to obtain the electron-density distribution around the H atoms, two X-(X+N) refinements were performed. In the first one (XL-Na refinement), the H-atom multipolar expansion was extended up to the quadrupolar term, as recommended by Chandler & Spackman (1982). In the other refinement (called XL-Nb), the multipolar expansion was truncated at the dipolar level.…”
Section: Refinements Against X-ray Datamentioning
confidence: 99%